HUBUNGAN ANTARA CONFUSED IDENTITY DENGAN PERILAKU AGRESIF REMAJA PADA SISWA SMP NEGERI 22 KELAS VII PALEMBANG - Siswoyo Siswoyo; Yuliansyah Yuliansyah (Psikis : Jurnal Psikologi Islami, 2016)
The purpose of this study was to determine whether there is relationship identity confused with aggressive behavior of adolescents Junior High School (SMP) 22 countries Palembang class VII. While the research hypothesis is that there is a positive relationship between identity confused with aggressive behavior of teenagers in SMP 22 countries Palembang.The variables of this study was confused identity and adolescent aggressive behavior. The population in this study are students (SMP) 22 countries Palembang totaling 270 students, the number of samples taken 45 students were determined using ramdon Sampling. Be Used collection instruments in this research is scale and scale identity confused adolescent aggressive behavior.Methods of data analysis using Pearson Product Moment of Pearson. Based on this analysis, showed no significant positive correlation between identity confused with aggressive behavior of teenagers at high school students (SMP) 22 countries Palembang with a correlation coefficient of 0.916 with a significance level by 0.05. That is, the higher the confused identity, the higher the aggressive behavior in adolescence.